PERGESERAN TERJEMAHAN PEMARKAH KOHESI ELIPSIS DALAM PENERJEMAHAN NOVEL SISTERS KARYA DANIELLE STEEL KE BAHASA INDONESIA - Iriana Sari, Christina Maya (Widya Warta, 2015)
This research is a study on the translation of ellipsis cohesion markers. It focusses on the types of ellipsis and the translation shift of ellipsis cohesion markers, the translation techniques applied and their effects on the translation shift, and the accuracy of the translation of ellipsis cohesion markers. It is a descriptive qualitative, single-case, and embedded research. The source of data consists of documents (novel Sisters and its translation) and informants (raters). The data were collected using document analysis, questionnaire and interview. The sampling technique is purposive sampling technique. The total data of ellipsis cohesion markers in the novel are 212 data. There are three types of ellipsis found in the novel Sisters, they are nominal ellipsis (51 data/ 24,28%), verbal ellipsis (36 data /17,14%), and clausal ellipsis (123 data/ 58,57%). The shift of cohesion types might occur in the translation of ellipsis cohesion markers. There are eleven techniques applied in the translation of ellipsis cohesion markers, such as amplification, literal, transposition, deletion, compensation, reduction, addition, modulation, borrowing, established equivalent, and adaptation. The meaning transfer in the translation of ellipsis cohesion markers in novel Sisters is carried out succesfully. 190 data (89,62%) are translated accurately, 19 data (8,96%) are translated less accurately, and 3 data (1,41%) are translated inaccurately.